iMpuma-Koloni / Eastern Cape, Part 2 - Truscott, Ross; Pohlandt-McCormick, Helena; Minkley, Gary (Kronos: Southern African Histories, 2024)
Background: There are two signs at the side of the road leading away from Salem, a small town in the Eastern Cape that has been at the centre of one of the most contentious land claim trials before South Africa’s Constitutional Court. The first reads: ’Welcome to Frontier Country’. The second: ’Potholes ahead’. The potholes offer themselves as further signs, but perhaps only in the way an inkblot solicits a transferential reading. What do potholes signify? Infrastructural disintegration? Erosion in the connective tissues of the region? Perhaps for some they are marks of social division associated with everything ’the frontier’ has come to signify.